IMPLEMENTATION OF NEW TECHNOLOGIES IN THE AEROBICS PROGRAM FOR FEMALE STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - Muratova Gulnara Rashitovna; Atadjanov Asadbek Baxtiyor o'g'li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Physical culture" in universities is characterized by a desire to develop and implement new ways of improving the health of students, which is caused by a large number of students with impaired health who attend physical education classes as part of special medical groups. At the same time, if physical education is taught in the main educational department in accordance with the Approximate Program for universities, then there is no such program for a special department, which forces departments to independently develop program materials, and in some universities generates the practice of mastering the discipline.